PENURUNAN TINGKAT PARTISIPASI PEMILIH PADA PEMILIHAN GUBERNUR RIAU TAHUN 2013 PUTARAN KEDUA (Studi di Kelurahan Rejosari dan Kelurahan Kulim) - Nurdiana "; Muchid " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Enacting Undang-Undang No. 32 tahun 2004 to the beginning of the implementation of local elections. On September 4th 2013 gubernatorial election held of Riau that have five pairs of candidates. However, in the first round of voting no one candidate won the election, so that the second round of the election held on November 27th 2013, which was have two pairs of candidats who have the most votes in the first round. In the second round, the level of public participation is lower than the first round. Data showed an increase in the number of voters who abstain from voting or non-voting highest in Tenayan Raya highway with the number increased is 7,79%. Recapitulation’s data of vote counting in the district Tenayan Raya, taken two villages that showed the highest increase in non-voting and non voting lowest increase, the villages are Rejosari and Kulim.This research is a field research by combining quantitative and qualitative approaches, where all the symptoms observed, measured and reaized in numbers and analyzed in descriptively. The result showed sociological factors, psychological, and rasional are factors that affect the decline in voter participation. At Rejosari village, rational factor is the factor most affecting of non-voting as many as 68,67%. Whereas psychological factors are the factor that most influence on the Kulim village, as many as 75,33%.Keyword: Non Voting, Voters Participation, Gubernatorial Elections